(untitled) (Raparin Journal of Humanities (RJH), 2025)
This study deals with the life of Mulla Abudlrahim Al-jaristani, who lived during the late Ottoman era between (1854-1916)’ in political and difficult security conditions, which was accompanied by the fall of the Ottoman Empire. Gaining knowledge and making use of it for writing, he spent a life full of toil and hard working. Further, Mulla Abdulrahim’s efforts were not limited only to teaching as he left after him numerous books in different branches of Islamic sciences indicating his extensive knowledge and wide-ranging insight. These works were not merely marginal notes on the books in circulation scattered throughout manuscripts; rather, he composed independent texts and commentaries, one of which was a treatise on the science of inheritance which was composed of an introduction, five sections, and a conclusion. including a treatise on inheritance law with an introduction, five sections and a conclusion. The introduction gives the definition to inheritance and the shares among the heirs besides dividing the inheritance into two groups (those who have fixed shares and those who inherit by agnation), explains what inheritance depends on, its impediments, the definition of ‘hijab’ (blocking in inheritance), and its types. The first section comes across heir’s condition whereas the second section talks about the order of the disposition of the estate and the order of the hairs. Third section deals with the fundamental principles of the scholarly issues, adjusting, balancing, or compensating the shares or parts in inheritance distribution when shares do not divide evenly, and correcting the distribution. Fourth section is about grandfather and siblings while the fifth section concentrates on distribution of inheritance through multiple deceased persons (Al-Munasakhat). The conclusion covers inheritance of the missing person, unborn (the fetus), and unclear (problematic) cases. Ultimately, the study focuses on addressing the life of Mulla Abudlrahim, thoroughly exploring the scientific and practical aspects of his life, editing this study, taking care of it, and extracting its text as intended by the author or as close to it as possible. It is considered the first thesis to address these two matters, as there were no previous studies on the life of the author. Its verification relied on the original handwritten manuscript in the author’s own handwriting.